England's Jewish solution experiment and expulsion, 1262-1290 - Mundill, Robin R. (Cambridge studies in medieval life and thought, 1998)
This is a detailed study of Jewish settlement and of seven different Jewish communities in England between 1262 and 1290, offering in addition a new consideration of the prelude to the expulsion of the Jews in 1290. The book estimates the extent of Jewish residence and settlement; evaluates the tallage payments made by those communities; and finally by a close discussion of prevailing attitudes towards usury and moneylending considers the Edwardian experiment of 1275. The impact of Edward I's legislation and Jewish policy on his Jewish subjects is then examined. It is possible to follow the business transactions of Jewish financiers in these different provincial communities over almost thirty years; and a thorough and detailed study is made of the type of people who borrowed from the Jews. Finally a survey is made of the possible motives and continental parallels which influenced the expulsion in 1290 and the subsequent dissolution